2022
DOI: 10.1002/cpz1.568
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic 3D Combinatorial Generation of hPSC‐Derived Neuromesodermal Organoids With Diverse Regional and Cellular Identities

Abstract: Neuromesodermal progenitors represent a unique, bipotent population of progenitors residing in the tail bud of the developing embryo, which give rise to the caudal spinal cord cell types of neuroectodermal lineage as well as the adjacent paraxial somite cell types of mesodermal origin. With the advent of stem cell technologies, including induced pluripotent stem cells (iPSCs), the modeling of rare genetic disorders can be accomplished in vitro to interrogate cell‐type specific pathological mechanisms in human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…We have also found that for some challenging disease hPSC lines an additional troubleshooting step to Stage 0 aggregation recipe may call for the early application of the GSK3b inhibitor, CHIR99021 (3 μM final), which acts to stimulate proliferation by canonical Wnt pathway activation. However, it has previously been established that prolonged exposure to FGF2 and Wnt signaling can cause hPSCs to drift towards a caudal neuromesodermal progenitor identity (Whye et al, 2022); therefore, if this troubleshooting approach is utilized then it is suggested that sustained FGF receptor inhibition (by SU-5402) is followed for the full duration of the 7-day neural induction phase in Stage 1. 3D neural spheroids can be characterized at Day 7 by immunostaining for the markers SOX1, SOX2, PAX6, and NESTIN (Table 1).…”
Section: Understanding the Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have also found that for some challenging disease hPSC lines an additional troubleshooting step to Stage 0 aggregation recipe may call for the early application of the GSK3b inhibitor, CHIR99021 (3 μM final), which acts to stimulate proliferation by canonical Wnt pathway activation. However, it has previously been established that prolonged exposure to FGF2 and Wnt signaling can cause hPSCs to drift towards a caudal neuromesodermal progenitor identity (Whye et al, 2022); therefore, if this troubleshooting approach is utilized then it is suggested that sustained FGF receptor inhibition (by SU-5402) is followed for the full duration of the 7-day neural induction phase in Stage 1. 3D neural spheroids can be characterized at Day 7 by immunostaining for the markers SOX1, SOX2, PAX6, and NESTIN (Table 1).…”
Section: Understanding the Resultsmentioning
confidence: 99%
“…An overview of the 35-day accelerated 3D cortical organoid differentiation process is depicted by the schematic in Figure 1. The method for generating 3D aggregate suspensions from pluripotent stem cells is as previously described (Whye et al, 2022); however, the media recipes differ. The initial step for cortical organoid generation requires aggregation of hPSCs in a FGF2-rich stem cell medium for a period of 24 hr to generate robust, homogenous populations of spheroids.…”
Section: D Hpsc Neural Inductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3D aggregates that broke symmetry formed extensions along the AP axis with organized germ layers 83 , 84 . Through the development of the technology of generating human gastruloids, specific gastruloids that addressed parts of the early stages of post-implantation human embryonic development were created, such as the processes of primitive streak formation 80 , neurulation 84 86 , and somitogenesis 87 .…”
Section: Early Gastruloids Recapitulating the Formation Of Three Germ...mentioning
confidence: 99%
“…Yet, few models are available to study pathologies with atria-, conduction tissues-, or ventricles-specific implications ( Lemme et al, 2018 ; Zhao et al, 2019 ; Kerr et al, 2021 ; Williams et al, 2021 ; Krause et al, 2022 ). Moreover, there is nevertheless a paucity of in vitro platforms of innervated cardiac muscle ( Whye et al, 2022 ), which could be essential to study the diseases, in which the impairment of the autonomic nervous system has tremendous effects on heart function, as in the case of Alzheimer syndrome and other neurodegenerative diseases ( Elia and Fossati, 2023 ). The progressive development of specific protocols to enrich CM subpopulations during hiPS differentiation ( Cyganek et al, 2018 ; Kerr et al, 2021 ) will not only solve the issues of graft unfunctional behavior described before but will further help to generate chamber-specific pathology models, also for rare congenital diseases.…”
Section: Unmet Needs and Issues To Be Addressed For Clinical Translationmentioning
confidence: 99%